TRADISI BARA’AN DALAM MASYARAKAT DESA TELUK PAMBANG KECAMATAN BANTAN KABUPATEN BENGKALIS - Pebri Karisma; Muhammad Razif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Pambang bay village is located in the District Rural Bantan Bengkalis and includedinto the Malay cultural social, Pambang in Bay Village, there is a unique tradition istradition Bara'an are held once a year just in the celebration of Eid, is the originBara'an words from Malay language meaning "Entourage" historical emergence ofthis tradition is that Bara'an in 1911 as time goes by they keep running traditionBara'an that they live in their home countries with the aim to strengthen thebrotherhood and solidarity and foster a sense of camaraderie. The purpose of thisstudy is the first to find out what function the tradition of the Bara'an tradition for thevillagers in the Gulf Pambang and second objective is to determine what it means forthe people of Bay Village Pambang about Bara'an tradition which has been for manyyears. Analyzing the data in this study using Qualitative Research Methods,Qualitative Research Methods This is an analysis that seeks to provide a detailedpicture of reality based on facts obtained from the field and also supported by thedata in order to support the primary and secondary data exist. Qualitative research ispresented in the form of words from the interview with the author of the respondentsthat describe the specific circumstances and understandable about the changeBara'an tradition about the function of tradition Bara'an itself is not runningoptimally and are not able to dampen social jealousy that occur in society andmeaning contained within the traditionKeywords: Tradition Bara'an, Bengkalis